The role of activated carbon size in the catalytic cracking of naphthalene. (1st January 2020) - Parrillo, F.; Ruoppolo, G.; Arena, U.
Abstract: Activated carbons are efficient catalysts for tar cracking, suitable for hot cleaning of the syngas produced during biomass- and waste-to-energy gasification processes. This study investigates the conversion of naphthalene, utilised as reference for tar compounds, when catalysed by a coal-derived activated carbon. The attention focuses on the influence of the operating temperature, in the range 750–900 °C, and the size of selected activated carbon, which has been used under form of pellets, granules and powders. The conversion efficiency improves when the temperature raised from 750 °C to 900 °C (from 79% to 99%, for the pellets), and when the catalyst size reduced from pellets to powders (from 79% to 97%, at 750 °C). The diffusional resistance in the catalyst particles has been then quantified in terms of Thiele modulus and internal effectiveness factor. A gradual reduction of catalyst surface area has been also observed for longer tests, due to the progressive deposition of soot from naphthalene decomposition over and inside the porous structure of the activated carbon. The carbon content of these deposits has been quantified, showing larger percentages on the surface of granules and powders. Highlights: Naphthalene is used as reference compound for tars in the syngas from gasification. Operating temperature and catalyst size have been investigated. Results indicate a pore diffusion resistance in coarser particles. Catalyst powders have limited pore diffusion resistance and do not lead to high pressure drops. Progressive reduction of the catalytic surface area is related to soot deposition.